'Wanting more from Mr. Eliot': Muriel Rukeyser, T. S. Eliot, and the Uses of Poetry. Issue 7 (9th August 2018) - Däumer, Elisabeth
ABSTRACT: Despite disagreements with T. S. Eliot's politics, Muriel Rukeyser was a serious student of Eliot's poetry, prose, and plays for much of her life, sharing his interest in poetry's communicative power and the novel ways in which modern poetics call for the mental, emotional, and physiological participation of readers. The Life of Poetry (1949), in conjunction with her five Vassar Lectures, assembled as 'The Usable Truth: Five Talks on Communication and Poetry', offers a complex view of her attitude toward Eliot, suggesting her sustained and critical engagement with his creative and critical work, in particular his concern with the communicative effectiveness of modern poetry; his poetic use of innovative cinematic techniques to reach readers in emotionally and intellectually exacting ways; his changing understanding of modern audiences; and his interest in the social uses of poetry, which motivated his turn to verse drama. Rukeyser's political and aesthetic radicalism, which informed her engagement with T. S. Eliot, was importantly shaped by her undergraduate experience at Vassar and friendship with Hallie Flanagan, whose experimental theatre impressed upon Rukeyser the democratising potential of avant-garde theatre, a lesson she sought to transpose to poetry.